2018
DOI: 10.1093/biolre/ioy177
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF1 signaling regulates the mitochondrial biogenesis markers in steroidogenic cells of prepubertal testis, but not ovary†

Abstract: Controlled changes in mitochondrial biogenesis and morphology are required for cell survival and homeostasis, but the molecular mechanisms are largely unknown. Here, male and female prepubertal mice (P21) with insulin and IGF1 receptors deletions in steroidogenic tissues (Insr/Igf1r-DKO) were used to investigate transcription of the key regulators of mitochondrial biogenesis (Ppargc1a, Ppargc1b, Pparg, Nrf1, Tfam) and architecture (Opa1, Mfn1, Mfn2) in Leydig cells, ovaries and adrenals. Results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…The results of this study showed that knockdown of GHR and the accompanying low expression of IGF1 could reduce the number of mitochondria and alter the structure of mitochondria, as observed in DF-1 cells as increased mitochondrial vacuolation, an absence of dense matrix granules and the disappearance of mitochondria cristae. Our results are in agreement with a previous study showing that a change in IGF1 signaling could alter the morphology and structure of mitochondria in mice Leydig cells [10].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this study showed that knockdown of GHR and the accompanying low expression of IGF1 could reduce the number of mitochondria and alter the structure of mitochondria, as observed in DF-1 cells as increased mitochondrial vacuolation, an absence of dense matrix granules and the disappearance of mitochondria cristae. Our results are in agreement with a previous study showing that a change in IGF1 signaling could alter the morphology and structure of mitochondria in mice Leydig cells [10].…”
Section: Discussionsupporting
confidence: 94%
“…Knockout of GHR (GHRKO) in mice could also alter the expression of key regulators of mitochondrial biogenesis [8,9]. Furthermore, previous studies have reported that insulin-like growth factor 1 (IGF1) signaling can regulate mitochondrial biogenesis markers in the steroidogenic cells of prepubertal testis [10], and is essential for mitochondrial biogenesis in cancer cells [11]. These findings suggest that the GHR gene plays a pivotal role in mammalian mitochondrial function both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the methods used in the present study were previously reported by our group in more detail (for all references please see 16,17,64 as well as in Supplemental Material and Methods, and are outlined briefly here.…”
Section: Methodsmentioning
confidence: 99%
“…Testicular steroidogenesis is under a delicate control of a cohort of signals from mitochondria. The changes in the intratesticular environment have been observed to influence the mitochondrial homeostasis and dynamics in testicular steroidogenesis (Bjelic, et al, 2015;Radovic, et al, 2019;Shen, et al, 2016;Strauss, et al, 2009). Nevertheless, the key factors responsible for the modulation of mitochondrial homeostasis in activated LCs remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%